Spontaneous Tension Pneumothorax as a Complication of COVID-19 - Muhammad Umar Shahzad; Jennie Han; Mohammad Ishack Ramtoola; Vasileious Lamprou; Urmi Gupta (Case Reports in Medicine)
Key Clinical Message. Tension pneumothorax is an uncommon presentation in patients with SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2) or COVID-19 pneumonia. We present a case of tension pneumothorax in a patient with COVID-19 pneumonia and myocarditis. This was an unlikely diagnosis in a patient with no known underlying lung condition and no other precipitating factors such as barotrauma. In an acute deterioration of patients with SARS-CoV-2, it is important to always consider alternative diagnoses and repeat imaging.